Inbred-hybrid relationship and heterosis on agronomic traits in bi-color sweet and waxy corn - PATCHARIN PATTHAWARO; ABIL DERMAIL; SOMPONG CHANKAEW; SAKUNKAN SIMLA; KHOMSORN LOMTHAISONG; KAMOL LERTRAT; KHUNDEJ SURIHARN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Patthawaro P, Dermail A, Chankaew S, Simla S, Lomthaisong K, Lertrat K, Suriharn K. 2023. Inbred-hybrid relationship and heterosis on agronomic traits in bi-color sweet and waxy corn. Biodiversitas 24: 6351-6359. Maize hybrids become more acceptable than other cultivar types since they promise high yield and uniformity by exploiting the heterosis advantages. Numerous lines are to be crossed to obtain the promising hybrids, and the progenies must be tested in multi-environment trials. Handling large number of genotypes in routine work is resource intensive; thus, the question arises if hybrid prediction based on the mid-parent (MP) value is feasible to reduce the workload. This study aimed to investigate the reliability of MP values in hybrid prediction through simple linear correlation and to estimate the magnitude of heterosis on given traits in sweet-waxy corn. Six parental lines and 10 F1 hybrids were evaluated in Khon Kaen in the dry and rainy seasons (2021/2022). Genotype and the interaction between genotype and season were significant for all observed traits. Waxy corn genotype 8A3-B was a good combiner for yield and yield components. Heterosis was trait-dependent, and it could imply parental adaptation when the estimation was done in contrasting environments. We found that the MP value can be used to predict the hybrid performance for flowering times only, but this approach was not effective for the rest agronomic traits. Since commonly, maize improvements are regarding multiple favorable traits, the strategy to use MP as single factor in hybrid prediction was not reliable. Other approaches, either SCA alone or the sum of mid-parent GCA and SCA, could be implemented for hybrid prediction in future studies.